2021
DOI: 10.1021/acs.langmuir.1c01886
|View full text |Cite
|
Sign up to set email alerts
|

Wetting Kinetics of Molten Carbonate on Carbon

Abstract: The wettability of molten carbonate on carbon determines the electrochemical performances of high-temperature direct carbon fuel cells (DCFCs). However, a universal method to measure the high-temperature wettability of molten carbonate is absent and the wetting kinetics is not well understood. Herein, we develop a dispensed drop (DD) method to measure the wetting kinetics of molten carbonate (Li 2 CO 3 −Na 2 CO 3 −K 2 CO 3 , 43.5:31.5:25.0, molar ratio) on the carbon substrate at 450−750 °C under controlled at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Mugikura and Selman reported on the influence of the oxide-ion activity on the contact angle in carbonate melts, mentioning a selective adsorption of O 2– on metallic surfaces, resulting in the adherence of the melt to the metal and thereby a decrease in the observed contact angle. The importance of the oxide-ion activity in the wetting kinetics of molten carbonates has also been brought up elsewhere . Following these studies, the behavior observed in Figure can be better understood.…”
Section: Resultsmentioning
confidence: 99%
“…Mugikura and Selman reported on the influence of the oxide-ion activity on the contact angle in carbonate melts, mentioning a selective adsorption of O 2– on metallic surfaces, resulting in the adherence of the melt to the metal and thereby a decrease in the observed contact angle. The importance of the oxide-ion activity in the wetting kinetics of molten carbonates has also been brought up elsewhere . Following these studies, the behavior observed in Figure can be better understood.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, interface wetting is a reaction-induced dynamic wetting process. 69 Chen et al used graphite rods as working electrode to study the wetting behavior of carbon in the DCFC anode environment in molten carbonate and CO 2 atmospheres. Since graphite is more polarized in ionic liquids, the molten carbonate will not wet the original carbon surface.…”
Section: σ σ = − ( − )/ [ ] P P L 14 Smentioning
confidence: 99%
“…Schematic of the wetting mechanism of the molten ternary carbonate on the carbon surface in different gas atmospheres. 69 using components to predict the surface tension of a single or multicomponent liquid metal becomes possible, which is mentioned in 3.1.2.…”
Section: Ionic Radiusmentioning
confidence: 99%
See 1 more Smart Citation
“…The various microstructures, obtained due to salt impregnation into the graphite, are driven by the molten salt wettability thermodynamics at high temperature, while the salt is in molten state. 70,71 The molten salts that were characterized by low values of surface tension and small contact angles (CsCl and KCl, Fig. 1) formed dense homogeneous composites (Fig.…”
Section: Gnp-salt Compositementioning
confidence: 99%